Seepage and Consolidation Characteristics of Dredger Fill - Chen, Mengqiao (Scientific Journal of Technology, 2025)
The consolidation process of dredger fill is the process of soil particles from disorderly and irregular arrangement to orderly and regular arrangement until flocculation and formation of more stable soil structure. In the project, it is an urgent problem to shorten the sedimentation consolidation time and make the dredger fill change from the slurry state to the foundation with a certain bearing capacity as soon as possible. In view of this situation, the indoor simulation experiment was carried out. Under the condition of simulating the soil water ratio of the actual project, the relationship between settlement and pore water pressure with time was found, and a reasonable low vacuum reinforcement scheme was determined to prevent small soil particles and water in pores from blocking the drainage channel. The curve is drawn by the observation data of the settlement amount, pore water pressure and drainage amount of the experiment, and then the time effect characteristic of the dredger fill settlement is analyzed. The change of pore water pressure and settlement amount tends to be stable at the same time with the increase of time, and the dredger fill is basically consolidated at this time. Based on the analysis of the changes in soil microstructure, particle size, particle abundance, particle orientation and macro basic physical properties, the formation of aggregates greatly improves the macro physical properties in the process of soil particles’ transition from unstable to stable state, which is manifested in the reduction of water content and the increase of density.